Financial Doping in the English Premier League. Issue 3 (3rd July 2018) - Iorwerth, Hywel; Tomkins, Paul; Riley, Graham
Abstract: Whilst the relationship between money and success in elite sport is acknowledged, the exact nature, extent and implications of this relationship is one that has not been carefully examined. In this paper, we have three main aims. Firstly, to provide empirical evidence of the extent that money buys success in the English Premier League. Secondly, to evaluate this evidence from a sports ethics perspective, and finally, to discuss potential solutions to the problem. We argue that the evident performance advantage teams gain through financial investments is contrary to the spirit of sport as it undermines athletic excellence and the 'sweet tension of uncertainty of outcome' that is central to good competition. Consequently, financial investments in elite football ought to be regulated and controlled. We argue, however, that current attempts to do so (via Financial Fair Play Regulations) are inadequate as they focus on issues concerning financial health, rather than the health of the game in terms of spirit and fairness.